Activities related to inflammatory bowel disease management during and after the coronavirus disease 2019 lockdown in Italy: How to maintain standards of care. Issue 10 (12th January 2020) - Saibeni, Simone; Scucchi, Ludovica; Dragoni, Gabriele; Bezzio, Cristina; Miranda, Agnese; Ribaldone, Davide Giuseppe; Bertani, Angela; Bossa, Fabrizio; Allocca, Mariangela; Buda, Andrea; Mocci, Gianmarco; Soriano, Alessandra; et al.
Abstract : Background and aims: Restructuring activities have been necessary during the lockdown phase of the coronavirus disease 2019 (COVID‐19) pandemic. Few data are available on the post‐lockdown phase in terms of health‐care procedures in inflammatory bowel disease (IBD) care, and no data are available specifically from IBD units. We aimed to investigate how IBD management was restructured during the lockdown phase, the impact of the restructuring on standards of care and how Italian IBD units have managed post‐lockdown activities. Methods: A web‐based online survey was conducted in two phases (April and June 2020) among the Italian Group for IBD affiliated units within the entire country. We investigated preventive measures, the possibility of continuing scheduled visits/procedures/therapies because of COVID‐19 and how units resumed activities in the post‐lockdown phase. Results: Forty‐two referral centres participated from all over Italy. During the COVID‐19 lockdown, 36% of first visits and 7% of follow‐up visits were regularly done, while >70% of follow‐up scheduled visits and 5% of first visits were done virtually. About 25% of scheduled endoscopies and bowel ultrasound scans were done. More than 80% of biological therapies were done as scheduled. Compared to the pre‐lockdown situation, 95% of centres modified management of outpatient activity, 93% of endoscopies, 59% of gastrointestinal ultrasounds and 33% of biological therapies. Resumption of activities after the lockdown phase may take three to six months to normalize. Virtual clinics, implementation of IBD pathways and facilities seem to be the main factors to improve care in the future. Conclusion: Italian IBD unit restructuring allowed quality standards of care during the COVID‐19 pandemic to be maintained. A return to normal appears to be feasible and achievable relatively quickly. Some approaches, such as virtual clinics and identified IBD pathways, represent a valid starting point to improve IBD care in the post‐COVID‐19 era.